Peluang Terjadinya Immunoglobulin M Berdasarkan Analisis Binary Logistic Faktor Penularan Virus Dengue - Lukman Hakim; Damar Tri Boewono (ASPIRATOR - Journal of Vector-borne Disease Studies, 2011)
Abstract. Morbidity of dengue hemorrhagic fever is still high due to factors of transmissionhas not completely known yet, so that disease control be conducted based on the cases. Thisstudy aimed to obtain information about factors related to the status of IgM anti-dengue virus.Studies have been conducted in village Klayan district Gunungjati regency Cirebon usingcross sectional design. Variable study is 10 independent variables consist of 5 environmentvariables and 5 host variables, whereas dependent variable is status of IgM antidenguevirus. The resulting data were analyzed using bivariate and multivariate analyse todetermine relationship between independent with dependent variable. Of the 400 respondentssurveyed, 56% are known to live in crowded homes, 85% at home with the lighting isnot optimal, 41.5% in home with positive not covered water container, 96% at home withoptimum air temperature, 62% in homes with optimal air humidity, and 23.5% at home witha positive mosquito Aedes spp larvae. Respondents with outside the home activities in lowcategories are 51.5%, nutritional status is not normal are 34%, age group <5 years are10.5%, ever get DHF are 16%, and positive IgM anti-dengue virus are 17.5 %. Bivariateanalysis showed three independent variables are significantly associated with the dependentvariable, whereas the multivariate analysis was resulted two variables are significantly associatedwith the dependent variable. It was concluded, the variables which significantly associatedwith status of IgM anti-dengue virus are outside the home occupants activities, nutritionalstatus and age groups. The estimating of chances of anti-dengue virus IgM can becalculated based on the activities outside the home occupants and nutritional status variable.